Soccer in American culture : the beautiful game's struggle for status - White, G. Edward (Sports and American culture series., 2022)
"An explanation of why the sport of soccer failed to take root in the United States when it spread around much of the rest of the world in the late nineteenth and twentieth centuries, and why the sport has had a twenty-first-century renaissance in America"--